Two-weighted inequalities for Riesz potential in $p$-convex weighted modular Banach function spaces - Bandaliyev, R. A.; Guliyev, V. S.; Hasanov, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The main goal of this paper is to prove a two-weight boundedness for Riesz potential from one weighted Banach functionspace to another weighted Banach function space. In particular, we obtain a two-weight boundedness for Riesz potentialand find sufficient conditions on the weights for boundedness of Riesz potential in weighted Musielak – Orlicz spaces.